A phenomenological study: The dynamics of psychological well-being among mental health workers - Wiwik Asih Rahayu; Nurhadijah Tri Putri; Mirza Ainin Artyani; Sri Lestari; Gita Aulia Nurani (Proyeksi, 2026)
Mental health workers are a group that is particularly vulnerable to psychological distress. Limited availability of mental health personnel combined with excessive workload may adversely affect their psychological well-being, both at a personal level and in the delivery of mental health services. This study aimed to explore the dynamics of psychological well-being among mental health practitioner. A qualitative phenomenological approach was employed, with data collected through in-depth interviews with three participants. The findings indicate that the participants’ psychological well-being was generally stable, despite the presence of work-related stress in the form of pressure and ongoing challenges. Internal factors contributing to psychological well-being included self-acceptance, adaptability, effective stress management, and a sense of meaning in both work and life. External factors, including interpersonal relationships and professional commitment, served as supportive elements for the internal factors. Together, these internal and external factors functioned as a balance against work-related stress. The study further revealed that each participant developed personal strategies to maintain and regulate their psychological well-being.